RENAL DYSFUNCTION IN NON-ALCOHOLIC FATTY LIVER DISEASE COMORBIDITY WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Matrzayeva Sh.G. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: Chronic obstructive pulmonary disease (COPD) and non-alcoholic fatty liver disease (NAFLD) are often coexisting diseases. Their comorbidity is often accompanied by systemic inflammation, oxidative stress, and metabolic disorders. The combination of these diseases can have a negative effect on kidney function and lead to dysfunction. Pathophysiological mechanisms are explained by the increase of inflammatory mediators, increased oxidative stress, hypoxia and metabolic syndrome. This situation worsens the general functional state of the body and increases the risk of developing chronic kidney disease (CKD). Early detection of kidney dysfunction in the comorbidity of CKD and JABBYK and treatment based on a multifactorial approach play an important role in preventing complications.